Special Exercises For Concentrating and Their Effect on Shooting Accuracy In Penalty Area In Science Soccer Club - Abedulameer, Yousif; Qassim, Sabah; Habeeb, Sabhan (Journal of Physical Education, 2015)
The first chapter included the interlocution and the importance of the research. The importance lies in close range shots in the penalty area as well as the ability to concentrate attention in performing the skill. The problem of the study, the hypotheses and the aims are all discussed in this chapter. Chapter two included theoretical studies including the concept of attention, shooting skill in soccer, close range shots in penalty area, etc. Chapter three tackled the field procedures including using the experimental method, the selection of the subjects, tests used, etc. Chapter four displayed, discussed and analyzed the results that the researchers came up with in relation to identifying the effect of special exercises and concentrating attention to develop the accuracy of shooting in the penalty area. Chapter five included the conclusions and recommendations. The most important conclusion was that there is a development in the level of performance that came as a result of developing the results of shooting accuracy